2022
DOI: 10.1055/a-1839-5185
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors associated with detection of sessile gastric polyps in patients with familial adenomatous polyposis

Abstract: Background and study aims Gastric cancer (GC) is increasingly reported and a leading cause of death in patients with familial adenomatous polyposis (FAP). Identifying features in patients with FAP who harbor sessile gastric polyps, likely precursors to GC, may lead to alterations in endoscopic surveillance in those patients and allow endoscopic intervention to decrease the risk of GC. The aim of this study was to identify demographic and clinical factors in patients with FAP who harbor sessile gastric polyps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mutations in an area called “mutation cluster region”, located on exon 15, between codon 1285 and codon 1580, are associated with the most severe disease phenotype, with the presence, among others, of desmoid tumors, hepatoblastoma and papillary thyroid carcinoma [ 16 ]. Mankaney et al described in a retrospective study APC pathogenic variants in patients with and without upper gastrointestinal involvement affected by FAP; his group found an APC pathogenic variant to 5′ codon 1309 in 89% of patients with gastric cancer and sessile gastric polyps, with a cluster between codons 1061 and 1150 [ 17 ]. A milder form of the disease is present when APC mutations occur in the 3′ (codons 1581–2843) or 5′ region (codons 78–167) of the gene, called attenuated FAP (AFAP) [ 18 ].…”
Section: Genetic and Molecular Aspectsmentioning
confidence: 99%
“…Mutations in an area called “mutation cluster region”, located on exon 15, between codon 1285 and codon 1580, are associated with the most severe disease phenotype, with the presence, among others, of desmoid tumors, hepatoblastoma and papillary thyroid carcinoma [ 16 ]. Mankaney et al described in a retrospective study APC pathogenic variants in patients with and without upper gastrointestinal involvement affected by FAP; his group found an APC pathogenic variant to 5′ codon 1309 in 89% of patients with gastric cancer and sessile gastric polyps, with a cluster between codons 1061 and 1150 [ 17 ]. A milder form of the disease is present when APC mutations occur in the 3′ (codons 1581–2843) or 5′ region (codons 78–167) of the gene, called attenuated FAP (AFAP) [ 18 ].…”
Section: Genetic and Molecular Aspectsmentioning
confidence: 99%
“…Prior to or concurrent with a gastric cancer diagnosis on endoscopic evaluation, endoscopic features such as carpeting of proximal gastric polyposis, densely concentrated polypoid mounds in the fundus and body of the stomach (1–2 years before cancer diagnosis), and mucosal patches are commonly seen, which make it difficult for surveillance of the stomach for neoplastic lesions [ 19 , 20 ]. Yang et al in their 2020 guidelines, American Society for Gastrointestinal Endoscopy guideline on the role of endoscopy in familial adenomatous polyposis syndromes, recommend 3- to 6-month surveillance EGD with aggressive polyp sampling and endoscopic debulking of large gastric polyposis mounds because more stage I cancers were found with this protocol.…”
Section: Stomach Lesionsmentioning
confidence: 99%
“…In FAP patients, the focus has been on describing the duodenal lesions given their established cancer risk. However, the authors concluded that more care should be taken to carefully examine and describe gastric findings [ 19 ].…”
Section: Stomach Lesionsmentioning
confidence: 99%